New Classes of Non-normalized Meromorphically Multivalent Functions - Irmak , Hüseyin; Raina, R. K. (Sarajevo Journal of Mathematics, 2024)
Making use of certain differential operators, this paper introduces two new classes: M_m,n,δ^κ(q;p) and SK_m,n, δ^κ(q;p) which consist of non-normalized meromorphically multivalent funcons with complex coefficients in the punctured unit disk. A theorem is established concerning an inclusion property for the above classes, and in the concluding section, several consequences of the main result are pointed out. 2000 Mathematics Subject Classification. Primary 30C45; Secondary 32A20, 30A10